Triangular Fibrocartilage Characterization with Ultrashort Echo Time-T2* MRI: Insights from a Healthy Cohort - Sana Boudabbous; Hicham Bouredoucen; David Ferreira Branco; Stefan Sommer; Tom Hilbert; Pierre-Alexandre Poletti; Rares Salomir; Bénédicte Marie Anne Delattre (Life)
The objective of this study is to measure T2* relaxation time in the triangular fibrocartilage (TFC) disc in asymptomatic volunteers and evaluate its variation with factors such as age, hand dominance, sex, and ulnar variance, using a dedicated MRI sequence. The MRI protocol included anatomical sequences as well as a 3D ultra-short echo time (UTE)-T2* mapping sequence. A linear regression model was used to assess the potential influence of age, sex, and hand dominance on T2* values measured in the TFC disc and to evaluate the correlation between T2* values and ulnar variance. T2* relaxation time was positively correlated with age. The higher T2* relaxation times may reflect early degeneration of the fibrocartilage microstructure, which is associated with both biomechanical factors and the aging process. However, T2* was not significantly influenced by sex or hand dominance, nor was it correlated with ulnar variance (this later being limited by the fact that none of our subject had positive ulnar variance). In conclusion, UTE-T2* is a promising MRI technique showing positive correlation with age in the TFC of healthy subjects. These findings are a first step to establish normative T2* values and will help interpreting deviations observed in patient with suspected pathology in future studies.